A study of literatures: status of alcohol in cosmetic products from shariah views in Malaysia - Baharum, Nur Bahirah; Awang, Mohd Daud; Arshad, Syariena; Abd Gani, Siti Salwa (Laboratory of Halal Policy and Management Halal Products Research Institute Universiti Putra Malaysia, 2019)
Alcohol is an organic solvent that is widely used in the manufacturing industry, especially in food and beverage products. It is also widely used in cosmetic industries to produce products such as perfume, moisturizer and other personal care products. Despite its widespread application, discussions regarding the use of alcohol in cosmetics from the Shariah and scientific perspectives are still very limited. Thus, the main focus of the present study is to consider the halal status of alcohol as an ingredient in Shariah-based cosmetic products in Malaysia. The analysis focuses on different aspects of Shariah law and also draws on scientific findings from previous studies. Opinion from scholars in Shariah and scientific field are examined in this articles, and the different types of alcohol found in cosmetic products are also discussed.